2006
DOI: 10.1007/s11224-006-9126-x
|View full text |Cite
|
Sign up to set email alerts
|

Paradigms and paradoxes: Energetics of the oxidative cleavage of indigo and of other olefins

Abstract: Indigo is a unique organic compound in terms of its blue color and its multiple conjugated functional groups contained therein. We ask whether the enthalpy of its cleavage reaction into two isatin molecules reflects the novelty of either this color and/or the conjugated functionalities contained therein.Indigo, species 1, is quite unique among organic compounds. It has a unique "eponymic" blue color and extensive historic provenance and importance in numerous cultures in both the Western and Eastern hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In conclusion, even if, the major photodegradation product, isatin, is thermodynamically more stable than indigo, 33 we have confirmed that protected from light and in a dry environment, indigo is very stable. The central double bond may be the key for the extraordinary, and unexpected, stability of this organic molecule; it enables a very fast non-radiative deactivation process, from the excited to the fundamental state, locking the molecule and protecting it from photodegradation.…”
Section: Discussionsupporting
confidence: 67%
“…In conclusion, even if, the major photodegradation product, isatin, is thermodynamically more stable than indigo, 33 we have confirmed that protected from light and in a dry environment, indigo is very stable. The central double bond may be the key for the extraordinary, and unexpected, stability of this organic molecule; it enables a very fast non-radiative deactivation process, from the excited to the fundamental state, locking the molecule and protecting it from photodegradation.…”
Section: Discussionsupporting
confidence: 67%
“…As such, the enthalpy of formation of thioindirubin is thus asked for, noting that the enthalpy of formation of indigo has been measured [248], albeit some 120 years ago. We note that the latter quantity was discussed in a recent study of the energetics of C=C bond cleavage for a variety of olefins [249] and so redetermination of this value is welcomed as well.…”
Section: Issuementioning
confidence: 89%
“…In this case, it is suggestive that O 2 should also be this state, even though that was not assumed in Ref. [1], and hence it will not be assumed here either.…”
Section: Introductionmentioning
confidence: 93%
“…Recently [1] we discussed the energetics of the oxidative cleavage of symmetric olefins, i.e. the enthalpy of the formal reaction…”
Section: Introductionmentioning
confidence: 99%